1994
DOI: 10.1002/ijc.2910590612
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for childhood brain tumors in the ILE DE France

Abstract: A case-control study investigating risk factors for childhood brain tumors was conducted in the Ile de France (Paris region). During a 2-year period (1985-1987) 109 newly diagnosed cases were identified and, of these, 75 could be interviewed. In the same region, 113 population controls, frequency-matched for year of birth, were interviewed. Odds ratios adjusted for child's age and sex and for maternal age were estimated for each risk factor present in utero or during childhood by conditional logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
5
10

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 16 publications
7
108
5
10
Order By: Relevance
“…As was the case in this study, the previous studies did not evidence any association between birth order and childhood CNS tumour [15][16][17][18][19][20][21][22][23][24][25]. The association between embryonal tumours and second born children observed in the present study was isolated, with no linear trend with increasing birth order, and would appear to have no particular biological plausibility.…”
Section: Discussionsupporting
confidence: 43%
“…As was the case in this study, the previous studies did not evidence any association between birth order and childhood CNS tumour [15][16][17][18][19][20][21][22][23][24][25]. The association between embryonal tumours and second born children observed in the present study was isolated, with no linear trend with increasing birth order, and would appear to have no particular biological plausibility.…”
Section: Discussionsupporting
confidence: 43%
“…Schwartzbaum et al, (1991) reported no association between parental use of pesticides in the garden between birth and diagnosis of Wilms' tumour (OR = 0.7, P = 0.30), whereas Olshan et al (1993) found a significant association between this tumour and household extermination of insects or pests in the 3 years before diagnosis (OR = 2.2, 95% CI = 1.2-3.8). Other studies have suggested that living on a farm during childhood or exposure to pesticides within the home environment may be associated with childhood bone cancer, brain cancer and leukaemia (Gold et al, 1979;Lowengart et al, 1987;Schwartzbaum et al, 1991;Buckley et al, 1994;Cordier et al, 1994;Leiss and Savitz, 1995;Meinert et al, 1996) and environmental pollution with pesticides has been suggested as a possible cause of childhood leukaemia in The Netherlands (Mulder et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Non-signi cant elevations in risk for CBTs have been reported in association with fathers' smoking (17,18) and mothers' smoking during pregnancy (2,7). A signi cantly elevated risk and dose-response relationship for CBTs has been found among children of non-smoking mothers exposed to passive smoking during pregnancy (2).…”
Section: Discussionmentioning
confidence: 99%
“…Although risk of CBTs has been reported to increase with maternal exposure to passive smoking during pregnancy (1,2), many studies have found no effect of parental smoking on the development of CBTs (3)(4)(5)(6)(7)(8)(9)(10)(11). The potential relationship between parents' alcohol consumption and CBTs has been less well studied: a positive association between beer drinking and CBTs has been noted (10,12), while other studies have been negative (1,13).…”
Section: Original Articlementioning
confidence: 99%